Factor VIII Inhibitors in Previously Treated Haemophilia A Patients with a Double Virus-inactivated Plasma Derived Factor VIII Concentrate - Peerlinck, K; Arnout, J; Di Giambattista, M; Gilles, J G; Laub, R; Jacquemin, M; Saint-Remy, J M R; Vermylen, J (Thrombosis and Haemostasis, 1997)
Antibodies to factor VIII (inhibitors) are usually produced at the beginning of treatment with factor VIII and are rare in multitransfused patients. Such antibodies are deemed to be patient-related, as supported by the description of a number of associated risk factors. However, a second category of inhibitors has recently been identified, namely antibodies occurring in multitransfused patients as a result of exposure to a particular factor VIII concentrate. A first outbreak of product-related inhibitors was recently described. The present paper describes the second well-documented occurrence of such inhibitors.Eight out of 140 multitransfused patients with severe haemophilia A developed an inhibitor to factor VIII shortly after changing treatment to a double-virus inactivated plasma-derived factor VIII concentrate. In addition to solvent-detergent treatment, this concentrate was pasteurised at 63° C for 10 hours. Exposure to the pasteurised product before inhibitor detection ranged from 9 to 45 days. Inhibitor titers varied between 2.2 and 60 Bethesda Units and recovery of transfused factor VIII ranged from 0.21 to 0.68 (expressed as IU/dl factor VIII rise per IU/kg administered). In contrast to usual inhibitors in haemophilia A patients, these product-related inhibitors showed complex inhibition kinetics. They were found specific for the factor VIII light chain. The inhibitors gradually declined when exposure to the pasteurised product was stopped, despite further treatment with other factor VIII concentrates. The present data stress the importance of carefully monitored clinical studies, both in previously treated and previously untreated patients, before introduction of a new or modified clotting factor concentrate.